The Dynamic Impacts of Interest Rate Volatility and Spillover Effect of the U.S. Policy Rate on the Banking Sector Development: Evidence from Selected Emerging Economies - Almahadin, Hamed Ahmad Mahmoud (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This thesis aims to investigate the dynamic impacts of local interest rate volatility and spillover effect of the U.S. policy rate on the banking sector development (BSD) of emerging countries during the period of 1980-2014. The bounds testing within the autoregressive distributed lag (ARDL) framework is employed using annual data. In addition, the Toda-Yamamoto of causality analysis has also been utilized. The findings suggest that the banking sectors of emerging countries are vulnerable to both local and international interest rates risks. The empirical results indicate that both local interest rate volatility and the U.S. policy rate have negative impacts on the majority of the suggested BSD indicators. These impacts continue to play a significant role in dampening path of the long-term convergence process for the BSD. The outcomes of causality analysis reveal that the U.S. monetary policy affects the BSD of the emerging countries through real interest rate channel. Therefore, these results could have important implications for policymakers to improve the banking systems and to promote economic growth in the sampled emerging economies.

ÖZ: Tez, 1980-2014 döneminde yıllık veriler kullanılarak yerel faiz oranındaki oynaklığın ve ABD politika faiz oranının yükselen ülkelerin bankacılık sektörü gelişimine (BSD) yansıyan dinamik etkilerini araştırmayı amaçlamaktadır. Çalışmada, ARDL (autoregressive distributive lag) eşbütünleşme yöntemi olarak bilinen sınır testi yaklaşımı kullanılmıştır. Ayrıca, Toda-Yamamoto nedensellik analizi de uygulanmıştır. Elde edilen bulgular, gelişmekte olan ülkelerin bankacılık sektörlerinin hem yerel hem de uluslararası faiz oranı risklerine karşı savunmasız olduklarını göstermektedir. Ampirik bulgulara göre, hem yerel faiz oranı oynaklığı hem de ABD politika faiz oranı BSD göstergelerinin çoğunu olumsuz etkilemektedir. Sözkonusu negatif etki, BSD için uzun vadeli yakınsama sürecinin yavaşlatılmasında önemli rol oynamaya devam etmektedir. Nedensellik analizinin sonuçları, ABD para politikasının gelişmekte olan ülkelerin BSD'sini reel faiz oranı kanalıyla etkilediğini ortaya koymuştur. Böylelikle, elde edilen ampirik bulguların örneklenen yükselen piyasa ekonomilerinde bankacılık sistemlerini iyileştirme ve ekonomik büyümeye katkı koyma bakımından politika yapıcılar için önemli olduğu düşünülmektedir.
Doctor of Philosophy in Banking and Finance. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Supervisor: Assoc. Prof. Dr. Gülcay Tuna Payaslıoğlu
Keywords: Banking and Finance; Saving and investment--United States; Interest (Income)--financial economics; Banking sector development; interest rate volatility; spillover effects; bounds test; ARDL approach; causality analysis; emerging economies